1982
DOI: 10.1136/bmj.284.6322.1081
|View full text |Cite
|
Sign up to set email alerts
|

Survival and desferrioxamine in thalassaemia major.

Abstract: Survival and desferrioxamine in thalassaemia major B MODELL, E A LETSKY, D M FLYNN, R PETO, D J WEATHERALL Abstract A small randomised trial and observation of all patients homozygous for beta-thalassaemia in Britain born in or before 1963 indicated that those patients who had received average weekly doses of more than 4 g of desferrioxamine over the previous few years were less likely to die in the near future than were patients of similar ages who had received less, or no, desferrioxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
5

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(74 citation statements)
references
References 12 publications
2
67
0
5
Order By: Relevance
“…[22][23][24] In our study chelation therapy with desferrioxamine was found to prevent the development of LVRFP, as reported by others. 25 On the other hand, Spirito et al did not find any influence of chelation therapy on the LV filling pattern.…”
Section: Discussionsupporting
confidence: 68%
“…[22][23][24] In our study chelation therapy with desferrioxamine was found to prevent the development of LVRFP, as reported by others. 25 On the other hand, Spirito et al did not find any influence of chelation therapy on the LV filling pattern.…”
Section: Discussionsupporting
confidence: 68%
“…The introduction of deferoxamine infusion in the 1970s had a profound effect on reducing mortality in TM, 2,277 and this was dominated by a reduction in iron overload-related cardiac mortality. More recently, deferiprone was introduced into clinical care in many countries (European approval in 1999 and US Food and Drug Administration approval in 2011), either as monotherapy or in combination with deferoxamine.…”
Section: Cardiac Mortality and Iron Chelationmentioning
confidence: 99%
“…W randomizowanym badaniu, przeprowadzonym wśród dzieci z TDT, porównywano deferoksaminę z placebo, uzyskując zmniejszenie wartości LIC do 25,9 mg/g suchej tkanki wątroby w porównaniu z 42,2 mg/g w grupie kontrolnej [60]. W badaniu włoskim, obejmującym 977 chorych na TDT, obserwowano mniej zgonów w grupie leczonej deferoksaminą niż w grupie otrzymującej placebo [61,62]. Co więcej, Brittenham i wsp.…”
Section: Monoterapia Chelatorami żElaza a Leczenie Skojarzoneunclassified
“…W 2000 roku Modell i wsp. [61] opublikowali wyniki rejestru retrospektywnego talasemii, w którym stwierdzono, że około 50% chorych na talasemię b umiera przed 35. rokiem życia, gdyż schemat leczenia jest zbyt uciążliwy, aby chory mógł w pełni współpracować i poddawać się leczeniu. Z kolei Kirk i wsp.…”
Section: Monoterapia Chelatorami żElaza a Leczenie Skojarzoneunclassified